Investigating Marketing Performance of Small Business in Kediri. Does the Role of Marketing Ambidexterity Matter? - Munawaroh, Nuril Aulia; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (Formosa Journal of Applied Sciences, 2023)
The objective of this research is to investigate the correlation between the development of market knowledge and cross-functional marketing capabilities, along with the concept of marketing ambidexterity. It aims to evaluate the factors that impact marketing performance in the handicraft industry in Kediri, East Java.   The research methodology employed in this study is quantitative research and a sampling was carried out using a non-probability sampling technique using 102 samples. The findings of this study demonstrate that market knowledge has a direct impact on enhancing cross-functional marketing capabilities, market knowledge can drive direct marketing ambidexterity and marketing ambidexterity can drive marketing performance. Firms must possess the capability to execute ambidexterity practices and talents within their respective marketplaces to attain exceptional performance.